Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s13046-018-0824-1
|View full text |Cite
|
Sign up to set email alerts
|

miR-182 suppresses invadopodia formation and metastasis in non-small cell lung cancer by targeting cortactin gene

Abstract: BackgroundMetastasis is the leading cause of cancer mortality and is a major hurdle for lung cancer treatment. Invadopodia, which are cancer-specific protrusive structures, play a crucial role in the metastatic cascade through degradation of the basement membrane and surrounding stroma. Cortactin, a critical component of invadopodia, frequently used as an invadopodia marker, a universally important player in invadopodia function, and is frequently overexpressed in cancer, but the exact mechanism of regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 44 publications
0
42
0
Order By: Relevance
“…CTTN has been confirmed as an oncogene and positive regulator of metastasis by previous study [ 25 27 ]. By bioinformatics predict that CTTN was a target gene of piR-19166 and there is one complementary binding site between piR-19166 and CTTN 3’UTR region.…”
Section: Discussionmentioning
confidence: 85%
“…CTTN has been confirmed as an oncogene and positive regulator of metastasis by previous study [ 25 27 ]. By bioinformatics predict that CTTN was a target gene of piR-19166 and there is one complementary binding site between piR-19166 and CTTN 3’UTR region.…”
Section: Discussionmentioning
confidence: 85%
“…Recently, numerous researches have shown that the degradation of extracellular matrix and basement membrane plays a decisive role in the invasion and metastasis of cancer cells. [ 15 17 ] Cell adhesion is the key to invasion and metastasis of cancer. [ 18 , 19 ] Increasing number of researches and experiments have found that cell adhesion molecules are closely linked to lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Src protein and RNA expression levels are significantly upregulated in most HBV + -HCC specimens and HBx transgenic mice, and the overexpression of Src promotes cell viability, migration, and cell colony formation [34][35][36] . The Src substrate CTTN has been found to be overexpressed in various cancers, including human colorectal cancer, esophageal tumors, and non-small-cell lung cancer, and HCC and CTTN overexpression closely correlates with tumor aggressiveness, cell adhesion, and cell motility [37][38][39][40][41][42] . We demonstrated that HBx contributed to cell migration and proliferation of HCC by binding CTTN in the cytoplasm and upregulating its expression.…”
Section: Discussionmentioning
confidence: 99%